Use of space technology for assisting water quality assessment and monitoring of inland water bodies - Toulios, Leonidas; Clayton, Chris R I; Hadjimitsis, Diofantos G.; Hadjimitsis, Marinos G. (My University, 2010)
Satellite remote sensing has been a valuable tool in providing a complete and synoptic geographical coverage of waterquality in fresh water systems. The principal benefit of satellite remote sensing for inlandwaterqualitymonitoring is the production of synoptic views without the need of costly in situ sampling. In addition spatial and temporal variations of waterquality and trophic state in fresh waterbodies such as dams and reservoirs can be mapped and assessed using satellite remotely sensed imagery. Satellite remote sensing techniques may also be used to design or improve in situ sampling monitoring programmes by locating appropriate sampling points based on the qualitative results obtained directly from the satellite images. A further benefit is the capability of establishing spectral statistical relationships of satellite data with waterquality parameters. Cyprus is made attractive by the frequency of high cloud-free imagery availability and moreover due to the fact that a single Landsat Thematic Mapper (TM) or Enhanced Thematic Mapper (ETM+) image of Cyprus covers almost the entire island. This paper examines the potential of using satellite remote sensing for the qualitative assessment of waterquality in inlandwaterbodies such as dams in Cyprus; including evaluation on spatial, temporal waterquality variations and finally an assessment on trophic state.
Keywords: Water quality; Dams; Space technology